Raba samostalnika pri gluhih učencih in učencih s polževim vsadkom - Globačnik, Bojana (Revija za elementarno izobraževanje, 2017)
The Use of Nouns By Deaf Students and Students with Cochlear Implant. Cochlear implants have fundamentally changed the rehabilitation and education of deaf people, particularly of children. Early operations in children make parents justifiably hopeful that following a successful early surgery and hearing and speech rehabilitation their child will be able to make up for their speech and language deficit by the time they enter school. The article provides an analysis of the use of nouns in sentences by a group of deaf students and a group of students with cochlear implants. The two groups were found to be quite equal in terms of their knowledge of the use of nouns. Out of all the age brackets, the best results were achieved by the students with cochlear implants in the second bracket (10– 12 years old), while deaf students without cochlear implants in the third bracket (12–16 years old) achieved better results in tasks involving the nominative case in plural and other cases in the singular grammatical number than students with cochlear implants. The study showed that for deaf students learning grammar is a difficult and gradual process.
Keywords: deaf students; students with cochlear implants; use of nouns in the singular and plural grammatical numbers